A comparative study of tragal cartilage and autologous incus for ossicular chain reconstruction in type IIB tympanoplasty at Dr. Hedgewar Hospital, Aurangabad - Deshmukh, Bharat G.; Bhisegaonkar, Deepak; Bakre, Akanksha (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: Tympanoplasty is the surgical operation performed for the reconstruction of the eardrum (tympanic membrane) and/or the small bones of the middle ear. Chronic otitis media is a very common condition of middle ear which not only has a high incidence in the world but also in our set up. So, in view of this, we decided to conduct a study on the surgical management of CSOM-tubotympanic type. Methods: We conducted this study at ENT department of Dr. Hedgewar Rugnalaya, Aurangabad to compare air bone gap closure by using tragal cartilage and autologous incus in type IIB tympanoplasty in patients with chronic suppurative otitis media, (tubotympanic). 66 patients with central perforation of tympanic membrane, necrosed incus and mobile stapes requiring type IIB tympanoplasty, were included as a part of the study. Results: We performed type IIB tympanoplasty with a routine post-aural incision in 66 patients. According to our observation, both incus and cartilage are good materials for ossiculoplasty, tragal cartilage being better. Conclusions: After conducting this study we concluded that incus and tragal cartilage both are excellent materials for ossiculoplasty.